2012
DOI: 10.5402/2012/245891
|View full text |Cite
|
Sign up to set email alerts
|

Biological Markers and Response to Neoadjuvant Taxane-Based Chemotherapy in Patients with Locally Advanced Breast Cancer

Abstract: Introduction. Biological markers as Her2/neu, p53, and hormonal receptors (HmRs) may be reliable parameters for prognostic assessment of patients of locally advanced breast cancer (LABC). This work aims at assessing the potential value of these biological markers for the prediction of disease outcome after neoadjuvant taxane-based chemotherapy and its implication on the surgical role. Patients and Methods. From March 2006 to September 2011, 95 patients with LABC were treated by neoadjuvant taxane-based chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
4
5
1
Order By: Relevance
“…Also, the incidence of luminal subtype was relatively higher than other reported cohorts (68%), with a relatively lower prevalence of TNBC (16.4%). This is in concordance with previous reports from Egypt [ 8 , 9 ], suggesting a profile of locally advanced breast cancer in Egyptian patients with younger age, more luminal disease, and more advanced clinical T and N stages. This, in part, explains the relatively higher rates of clinical response despite similar pCR rates compared to international studies [ 10 – 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…Also, the incidence of luminal subtype was relatively higher than other reported cohorts (68%), with a relatively lower prevalence of TNBC (16.4%). This is in concordance with previous reports from Egypt [ 8 , 9 ], suggesting a profile of locally advanced breast cancer in Egyptian patients with younger age, more luminal disease, and more advanced clinical T and N stages. This, in part, explains the relatively higher rates of clinical response despite similar pCR rates compared to international studies [ 10 – 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…The current investigation found that 10% of patients exhibited N0, 70% exhibited N1, and 20% had N2. This came to the same conclusion as El-Sayed et al 12 , who found that 20% of cases exhibited N0, 55% exhibited N1, and 25% exhibited N2.…”
Section: Discussionsupporting
confidence: 85%
“…This agrees with El-Sayed MI et al, study that stated that 20% of patients had N0, 55% of them had N1 and 25% of them had N2. 13 14,15 In this study 88% of patients had IDC, 2% of patients had ILC and 10% of patients had mixed ductal and lobular carcinoma. This agrees with Mashoori N et al, who stated that 91.2% of patients had IDC and 8.8% of them had ILC and close to the results of Rahman MS et al, study which stated that 80.45% were classified as IDC, 13.64% as ILC and 5.91% as mixed invasive patterns.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, 88% were ER/PR-positive and 12% were Her2-positive, this doesn't agree with Vieira RA et al, that stated that 61.5% were ER-positive, 52.6% were PR-positive and 23.1% were Her2-positive and close to the results of El-Sayed et al, study who stated that 21% of patients were Her2-positive and very near to results reported by Rahman MS et al, which stated that 69.09% were found estrogen receptor positive tumor. 13,16,19 According to response to chemotherapy, partial response was observed in (82%) of patients, complete response was detected in (14%) of patients and (4%) of them were presented with stationary disease, this agree with Rahman MS et al, study that stated that 18% had CR, 75% had PR and 7% had SD and agree with Salem MA et al, study that stated 9% had complete response, 79% had partial response and 10% had stationary disease and 2% had progressive disease. 15,16 In the present study, 22% of cases were complicated with seroma that was detected clinically and confirmed by U/S and wound infection occurred in 8% of them.…”
Section: Discussionmentioning
confidence: 99%